Factors Influencing Sustainable Tax - Lailatun Nafisa; Ida Harahap; Muhammad Rispan Affandi; Erawati Kartika; Yulistina (Indonesian Journal Economic Review (IJER), 2026)
This study examines the effect of leverage and profitability on sustainable tax, using the effective tax rate (ETR) as a proxy for manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2025. This study employs a quantitative research approach using secondary data obtained from manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2025. The sample consists of 310 observations of publicly listed manufacturing companies on the IDX, selected through purposive sampling. Data analysis was performed using SPSS®26. Analytical techniques included descriptive statistics, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and hypothesis testing. Partial results indicate that leverage and profitability influence sustainable tax, using the effective tax rate (ETR) as a proxy, in manufacturing companies listed on the Indonesia Stock Exchange in 2021-2025. Simultaneously, leverage and profitability influence sustainable tax, using the effective tax rate (ETR) as a proxy, in manufacturing companies listed on the Indonesia Stock Exchange in 2021-2025. This study contributes to the accounting literature and provides practical implications for regulators, managers, and investors.